PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, GROWTH OPPORTUNITIES DAN FINANCIAL DISTRESS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Yamin, Mohammad; Ramadhani, Yasmin (Accounting Research and Business Journal, 2024)
This study aims to determine the effect of managerial ownership, leverage, growth opportunities and financial distress on accounting conservatism. This research was conducted at manufacturing company sector consumption goods listed on the Indonesia Stock Exchange for the 2018-2022 period. The data used is secondary data in the form of financial reports taken from the company's official website and from the Indonesia Stock Exchange (www.idx.co.id). The selection of the research sample was carried out using a purposive sampling method. Obtained as many as 8 companies that have met the criteria with five years of research. The analytical method used is multiple linear regression method using SPSS 26.0. The results showed that partially managerial ownership and leverage had no effect on accounting conservatism, while growth opportunities and financial distress had a negative and significant effect on accounting conservatism. Simultaneously the variables of managerial ownership, leverage, growth opportunities and financial distress have a significant effect on accounting conservatism.